2022
DOI: 10.1002/chem.202200826
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzophenazine‐Based TADF Emitters as Dual Electrochromic and Electroluminescence Materials

Abstract: Previous work has reported the synthesis of donor–acceptor–donor molecules based on dibenzophenazine acceptor group, presenting thermally activated delayed fluorescent (TADF) properties and their application in the assembly of highly efficient electroluminescent devices. Herein, we focus on the characterisation of charge carrier species through UV‐Vis‐NIR spectroelectrochemical and potentiostatic EPR techniques, in addition to the investigation of electropolymerisation properties of some compounds depicted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…29 While it might be assumed that a single D−A unit is sufficient to ). 30 The appropriate choice of a host matrix [4,4′,4′′-tris(N-3methylphenyl-N-phenyl-amino)-triphenylamine: m-MTDA-TA] for the fabrication of an OLED-enabled near-infrared emission (λ em 741 nm) from an exciplex between the emitter and the host material is noteworthy (Figure 3e). This represents one of the earliest examples of near-infrared TADF from a TADF exciplex.…”
Section: Enhancing Ct Character For Efficient Tadf Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…29 While it might be assumed that a single D−A unit is sufficient to ). 30 The appropriate choice of a host matrix [4,4′,4′′-tris(N-3methylphenyl-N-phenyl-amino)-triphenylamine: m-MTDA-TA] for the fabrication of an OLED-enabled near-infrared emission (λ em 741 nm) from an exciplex between the emitter and the host material is noteworthy (Figure 3e). This represents one of the earliest examples of near-infrared TADF from a TADF exciplex.…”
Section: Enhancing Ct Character For Efficient Tadf Manifestationmentioning
confidence: 99%
“…The external quantum efficiency (EQE) of the device (DEV 3, Figure d) reached a very high value (16%) for orange TADF-OLED. Further optimization of device configurations by adding a hole injection layer (2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexa­azatriphenylene: HAT-CN) and removing an extra electron-transporting layer (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline: BCP) achieved an EQE close to the theoretical maximum (20.5%) …”
Section: Introductionmentioning
confidence: 96%
“… [7] In a device an external quantum efficiency of up to 0.205 could be achieved, making POZ‐DBPHZ a promising orange TADF emitter. [10] It was shown that the torsion angle between D and A units is nearly 90°. [5] This causes the required separation of electron and hole densities and reduces to 20 meV, highlighting the importance of three‐dimensional conformations.…”
Section: Introductionmentioning
confidence: 99%
“…One notable example is POZ‐DBPHZ, a D−A−D triad with two phenoxazine (POZ) moieties bridged by a central DBPHZ unit [7] . In a device an external quantum efficiency of up to 0.205 could be achieved, making POZ‐DBPHZ a promising orange TADF emitter [10] . It was shown that the torsion angle between D and A units is nearly 90° [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The most basic principle of electrochromic materials is their electron-transfer activity, in which molecules gain and lose electrons through REDOX reactions, presenting reversible color changes at different voltage values [ 14 , 15 , 16 , 17 ]. In the research, the process of natural selection is an inevitable process when developing materials; from the beginning stage of simple inorganic discoloration to the present organic oligomer’s structure, the field of electrochromic materials has experienced dramatic changes [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%